Practical RF circuit design for modern wireless systems. - Besser, Les, ....-; Gilmore, Rowan, ....- (Boston : Artech House, 2003)
The first of a two-volume set, this leading-edge book takes a practical approach to RF circuit design, offering a complete understanding of the fundamental concepts you need to know and use for your work in this industry. The book lays the ground work for efficient RF circuit design in a step-by-step approach, by defining important principles and parameters and progressively introducing critical analytical tools. It helps you distinguish between RF and low frequency circuits, and offers a detailed look at a typical RF system. This is a tested and insightful book that contains answers to most of the questions practical engineers are asking. The first volume reviews various computer-aided simulation, synthesis, and optimization techniques used in modern RF and microwave design, and discusses the practical use of the graphical design tools, such as the Smith Chart.
2: Active circuits and systems